Pengaruh Influencer Marketing dan Content Marketing melalui Akun TikTok Rucas terhadap Keputusan Pembelian Generasi Z di Kota Samarinda - Achmad Faris; Purwadi Purwadi (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of influencer marketing and content marketing through the TikTok account Rucas on purchasing decisions of Generation Z in Samarinda City. This study uses a quantitative approach with associative research type. The population is Generation Z in Samarinda City who use the TikTok platform and have seen content from the TikTok account Rucas. The sampling technique used purposive sampling with certain criteria, obtaining 100 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS. The results show that influencer marketing has a positive and significant effect on purchasing decisions with T-statistics of 12.418 (>1.96) and P-values of 0.000 (<0.05). Meanwhile, content marketing has a positive but not significant effect on purchasing decisions with T-statistics of 0.923 (<1.96) and P-values of 0.356 (>0.05). Simultaneously, both variables are able to explain purchasing decisions by 46.7%, while the remaining 53.3% is explained by other variables outside the research. These findings indicate that influencer marketing is more dominant in influencing purchasing decisions compared to content marketing. This research is expected to be a consideration for business actors in designing effective digital marketing strategies through the TikTok platform.